Does oil palm agriculture help alleviate poverty? A multidimensional counterfactual assessment of oil palm development in Indonesia. (August 2019) - Santika, Truly; Wilson, Kerrie A.; Budiharta, Sugeng; Law, Elizabeth A.; Poh, Tun Min; Ancrenaz, Marc; Struebig, Matthew J.; Meijaard, Erik
Highlights: Oil palm is promoted to alleviate poverty, despite limited social impact evidence. The social impacts of oil palm plantations are not uniformly positive nor negative. Improved welfare had occurred for plantations developed in market-based villages. The opposite was found for plantations developed in subsistence-based villages. Oil palm expansion in remote forest areas requires careful planning and evaluation. Abstract: Palm oil producing countries regularly promote the positive impact of oil palm agriculture on poverty alleviation, despite limited evidence about the contribution of this crop on village well-being. Past evaluations that quantify the social impact of oil palm are dominated by localized studies, which complicate the detection of generalizable findings. Moreover, only a few of these evaluations are based on rigorous case-control studies, which limits the robustness of the conclusions. Here we examined the association between the development of oil palm plantations and change in objective or material well-being between 2000 and 2014 across villages in Kalimantan, Indonesian Borneo. We applied a matching method to evaluate the impacts of oil palm plantations across different aspects of well-being, accounting for varying time delays in the accrual and realization of benefits after plantation development. Our study reveals that the social impacts of oil-palm plantations are not uniformly positive, nor negative, and have varied systematically with biophysical locations and baseline socioeconomic conditions of nearby communities prior to oil palm development. Plantations developed in villages with low to moderate forest cover, in which the majority of communities already relied on market-oriented livelihoods, were associated with improved socioeconomic well-being compared to villages without oil palm development. However, we found the opposite for plantations developed in remote villages with higher forest cover, in which the majority of communities previously relied on subsistence-based livelihoods. Overall, oil palm growing villages were more associated with reduced rate of improvement of social and environmental well-being compared to villages without oil palm development, regardless of location and baseline community livelihoods. Our findings highlight an urgent need for careful evaluation and planning in the development of oil palm agriculture in remote forested areas. For oil palm regions that have been developed, our study shows that unsustainable livelihoods, increased socioeconomic disparity, and environmental issues remain major challenges.